Understanding the role of the ground surface in HONO vertical structure: High resolution vertical profiles during NACHTT‐11. Issue 17 (5th September 2013) - VandenBoer, Trevor C.; Brown, Steven S.; Murphy, Jennifer G.; Keene, William C.; Young, Cora J.; Pszenny, A. A. P.; Kim, S.; Warneke, Carsten; de Gouw, Joost A.; Maben, John R.; Wagner, Nicholas L.; Riedel, Theran P.; et al.
Abstract : [1] A negative‐ion proton‐transfer chemical ionization mass spectrometer was deployed on a mobile tower‐mounted platform during Nitrogen, Aerosol Composition, and Halogens on a Tall Tower (NACHTT) to measure nitrous acid (HONO) in the winter of 2011. High resolution vertical profiles revealed (i) HONO gradients in nocturnal boundary layers, (ii) ground surface dominates HONO production by heterogeneous uptake of NO2, (iii) significant quantities of HONO may be deposited to the ground surface at night, (iv) daytime gradients indicative of ground HONO production or emission, and (v) an estimated surface HONO reservoir comparable or larger than integrated daytime HONO surface production. Nocturnal integrated column observations of HONO and NO2 allowed direct evaluation of nocturnal ground surface uptake coefficients for these species (γNO2, surf = 2 × 10 −6 to 1.6 × 10 −5 and γHONO, surf = 2 × 10 −5 to 2 × 10 −4 ). A chemical model showed that the unknown source of HONO was highest in the morning, 4 × 10 6 molecules cm −3 s −1 (600 pptv h −1 ), declined throughout the day, and minimized near 1 × 10 6 molecules cm −3 s −1 (165 pptv h −1 ). The quantity of surface‐deposited HONO was also modeled, showing that HONO deposited to the surface at night was at least 25%, and likely in excess of 100%, of the calculated unknown daytime HONO source. These results suggest that if nocturnally deposited HONO forms a conservative surface reservoir, which can be released the following day, a significant fraction of the daytime HONO source can be explained for the NACHTT observations. Key Points: HONO vertical gradients form on nights with stable nocturnal boundary layers Nocturnal HONO production consistent with ground surface area dominance Surface deposition of HONO may be a reservoir for the unknown daytime source